The importance of lizards and small mammals as reservoirs for Borrelia lusitaniae in Portugal - Norte, A. C. (2014)
Borrelia lusitaniae is a pathogen frequent in the Mediterranean area. Apart from lizards, evidence for birds and small mammals as competent reservoirs for this genospecies has been occasional. We collected questing ticks, skin biopsies and Ixodes sp. ticks feeding on lizards, birds and small mammals in a B. burgdorferi s.l. enzootic area to assess their importance in the maintenance of B. lusitaniae. B. lusitaniae was the most prevalent genospecies in questing ticks and was commonly found in larvae feeding on Psammodromus algirus. One biopsy infected with B. lusitaniae was collected from the tail of one Podarcis hispanica, which suggests systemic infection. I. ricinus larvae feeding on Apodemus sylvaticus were infected with B. lusitaniae but with a lower prevalence. Our results reinforce the importance of lizards as reservoirs for B. lusitaniae, suggesting that P. algirus, in particular, acts as main reservoir for B. lusitaniae in Portugal.